Troy Bolton’s linguistic characterization in high school musical: breaking free of the status quo on a linguistic level? - Bez, Tine (Heidelberg journal of English studies, 2025)
This paper investigates the linguistic construction of Troy Bolton’s character in High School Musical through a pragmatics-informed analysis of direct characterization. Drawing on distinctions between self-presentation and other-presentation, the study examines how explicitly verbalized information contributes to the shaping of the male protagonist’s on-screen identity. A systematically compiled transcript of the film serves as the basis for identifying instances of direct characterization, including clearly implied cases situated at the boundary between direct and indirect forms. The analysis reveals a striking asymmetry: while Troy’s social environment—his teammates, peers, and father—consistently characterizes him almost exclusively through the lens of basketball, Troy’s own self-presentation conveys a more multifaceted self-image. This discrepancy exposes tensions between entrenched societal expectations and the protagonist’s desire to “break free” from the status quo. To account for the film’s depiction of Troy’s gradual character development, the study further incorporates selected indirect cues, including conversational structure, address forms, and paralinguistic features. These additional layers illustrate how the narrative ultimately negotiates and resolves the conflict between imposed stereotypes and Troy’s emerging complexity.